PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI INDONESIA TAHUN 2006 - Sri Handayani (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
This research examines the disclosure level of local government’s financial report based on Government Accounting Standard (SAP), as dependent variable, and its relation to management incentives and audit finding and classification of localgovernment, as independent variable. Total samples for this research are 100 financial reports of municipality/regency (LKPD) for budgeting year of 2006. The criteria of samples are: (1) audited LKPDs for fiscal year 2006, (2) four components of financial report such as Budget Realization Report, Ballance Sheet, Cash Flow Reports and Budget Realization Notes. The checklist of notes to the financial statement based on SAP is used for scoring the level of disclosure. Multiple regression is used for testing the model. Statistically, the result shows that the intergovermental revenue and classification of local government does notsiginificantly influence the disclosure level based on SAP. However, wealth, government complexity, number of audit finding and level of departure does significantly influence the disclosure level based on SAP.